2003
DOI: 10.1034/j.1600-051x.2003.300102.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of novel low abrasive air polishing powders

Abstract: The novel air polishing powder D is of low abrasiveness to root cementum and dentin while being effective in removing dental plaque. Thus, it may be useful for safe and efficient plaque removal on exposed root surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
132
1
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(143 citation statements)
references
References 25 publications
(54 reference statements)
5
132
1
5
Order By: Relevance
“…With the goal of establishing an efficient and safe technique for subgingival biofilm removal, a low-abrasive air-polishing powder was developed for use in commercially available air-polishing devices [6][7][8] . This novel approach to biofilm removal substantially facilitates periodontal debridement.…”
Section: Introductionmentioning
confidence: 99%
“…With the goal of establishing an efficient and safe technique for subgingival biofilm removal, a low-abrasive air-polishing powder was developed for use in commercially available air-polishing devices [6][7][8] . This novel approach to biofilm removal substantially facilitates periodontal debridement.…”
Section: Introductionmentioning
confidence: 99%
“…It should be mentioned that deleterious effects of air abrasion or air polishing procedures with sodium bicarbonate powder on sound dentin and cementum have been noted 1,10) . However, it was recently reported that a low-abrasive air polishing powder, which was an improved product of the standard sodium bicarbonate powder, minimized the deleterious effects on sound dentin and cementum, while effectively removing dental plaque 11) . Indeed, the bicarbonate powder used in this study resulted in mild removal of carious lesions in the extracted human teeth, as compared with rotary instruments.…”
Section: Discussionmentioning
confidence: 99%
“…As a rule, it is known that it should be certainly avoided to use these devices on dentin and cement [25]. Tissue loss caused by the technique is depends on application time, powder and water application as much as the probe distance and the application surface [25,26].…”
Section: Journal Of Biomedical Sciences Issn 2254-609xmentioning
confidence: 99%
“…Tissue loss caused by the technique is depends on application time, powder and water application as much as the probe distance and the application surface [25,26]. While we used air powder instrument in our study, the application was done by the same researcher from 1-1,5 cm by approaching at a right angle to the tooth surface.…”
Section: Journal Of Biomedical Sciences Issn 2254-609xmentioning
confidence: 99%